Relationship Between the Competencies of Charge Nurses and Interprofessional Collaboration as Healthcare Team and the Effectiveness of Wards in Tertiary Care, General Hospitals of Health Region 8 - Sungkanak, Pornnapa; Juntachum, Wanchanok (Medical Journal of Sakon Nakhon Hospital, 2024)
This descriptive research aimed to study the relationship between competencies of charge nurses and interprofessional collaboration as healthcare team and the effectiveness of wards in tertiary care hospitals of health region 8. The samples were 206 registered nurses who were officially assigned to be charge nurses and selected by a multi–stage sampling method. The research instruments included the questionnaire about the effectiveness of wards, competencies of charge nurses and interprofessional collaboration as healthcare team with 5–level rating scale. The content validity of the questionnaires was measured by 5 experts. The reliability of the questionnaires about the effectiveness of wards, competencies of charge nurses with regard to expertise in profession, management, leadership and information and technology and the questionnaire about interprofessional collaboration as healthcare team measured by the Cronbach’s alpha coefficient were 0.92, 0.86, 0.87, 0.82, 0.81 and 0.97 respectively. Data were analyzed using the statistics, frequency, mean, percentage, standard deviation and Pearson’s correlation coefficient. The study results indicated that the charge nurses’ competencies in all aspects were at a high level; expertise in profession ( = 4.41, S.D. = 0.45) , management ( = 4.29, S.D. = 0.46), leadership ( = 4.21, S.D. = 0.49) and information and technology ( = 4.21, S.D. = 0.51). In average, the interprofessional collaboration as healthcare team was at a high level ( = 4.32, S.D. = 0.49). The average competencies of charge nurses and interprofessional collaboration as healthcare team were positively and significantly correlated with the effectiveness of wards at a high level (r = 0.811, p < 0.01 and r = 0.817, p < 0.01, respectively).